2016
DOI: 10.1016/j.ijosm.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of living with persistent back pain

Abstract: This Masterclass discusses findings from a growing body of qualitative research studies that have investigated the subjective experience of having persistent non-malignant low back pain. These studies have found that people with experience changes in self image, personal relationships and life roles. They have also reported on how subjectivity affects the therapeutic relationship, what patients have found helpful in dealing with healthcare professionals, and what it is like to go through a healthcare system fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…This may involve providing practitioners with clear guidance on how to balance the patient's psychosocial problems and the biomechanical approach in daily clinical practice, and the development of specific strategies of implementation in their clinical behaviours. This is consistent with the need to expand the scope of osteopathic practice towards a more embedded and embodied clinical reasoning process [26,38], considering patients' beliefs [81], pain control strategies, pain neuroscience education [50] and expand the adoption of multidisciplinary care [37].…”
Section: Discussionsupporting
confidence: 62%
“…This may involve providing practitioners with clear guidance on how to balance the patient's psychosocial problems and the biomechanical approach in daily clinical practice, and the development of specific strategies of implementation in their clinical behaviours. This is consistent with the need to expand the scope of osteopathic practice towards a more embedded and embodied clinical reasoning process [26,38], considering patients' beliefs [81], pain control strategies, pain neuroscience education [50] and expand the adoption of multidisciplinary care [37].…”
Section: Discussionsupporting
confidence: 62%
“…Pain is always subjective (10) and people learn and use it based on their individual life experiences. Griensven (11) studied the subjective aspects of experiencing chronic LBP and found that the long-term condition made patients feel trapped in the health system and despondent in the face of repeated treatment failures, resigned to a life of pain. The author reports that patient's pain and dysfunctional symptoms were invalidated when the initially enthusiastic healthcare professionals lost interest because treatment did not produce the expected results and they were unable to provide a clear explanation for the pain, leading to feelings of frustration and anxiety.…”
Section: Figg-lathammentioning
confidence: 99%
“…Furthermore, patients describe difficulties in social relationships and concerns regarding illness stigma, threatening their quality of life (Froud et al., 2014). Living with persistent pain can be experienced as isolating, unfair, feeling a lack of control and helplessness (van Griensven, 2016). Against the background of these manifold consequences of ongoing pain, this article will pay special attention to the stagnation of severe back pain.…”
Section: Introductionmentioning
confidence: 99%